STUDIES ON THE AUTONOMIC INNERVATION IN THE INTESTINE OF HYLA ARBOREA - SHARMA, VIJAY PRAKASH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
The distribution, structure and function of nerve fibres, nerve plexuses, nerve cells, nerve endings, ganglions and blood vessels in different layers viz, mucosa, submucosa, muscularis and serosa of intestine of H. arborea has been discussed and compared with other amphibians.